Doomsday Prepping During the COVID-19 Pandemic - Smith, Nina; Thomas, Susan Jennifer (Frontiers in Psychology, 2021)
“Doomsday prepping” is a phenomenon which involves preparing for feared societal collapse by stockpiling resources and readying for self-sufficiency. While doomsday prepping was traditionally associated with small numbers of extremists prepping for seemingly unlikely scenarios, during the COVID-19 pandemic, excessive stockpiling and panic-buying of resources has been globally widespread, leading to further shortages and distress. It is unclear what psychological or demographic factors are associated with this stockpiling. This study investigated doomsday prepping beliefs and behaviours in relation to COVID-19 proximity, demographics, coping strategies, psychopathology, intolerance of uncertainty (IU), and personality in 384 participants (249 female) in an online study. Participants completed questionnaires including the Post-Apocalyptic and Doomsday Prepping Beliefs Scale and the Prepping and Coping during a Pandemic Scale, a new scale designed to measure prepping in the context of COVID-19. These were analysed using ANOVAs, correlational, and mediation analyses to examine relationships between psychometric variables and stockpiling. Prepping beliefs and behaviours were higher in males than females and positively associated with anxiety, obsessive-compulsive symptoms, IU, and traditionally masculine personality characteristics. Older age, male gender, obsessive-compulsive symptoms, and traditional masculinity traits predicted unique variance in prepping. The relationship between gender and stockpiling was mediated by social learning (witnessing other people panic-buying) and the perceived threat of COVID-19 (doomsday interpretations) while proximity and personal vulnerability to COVID-19 were not significant. Results indicate that panic-buying was influenced more by witnessing others stockpiling, personality, and catastrophic thinking rather than by proximity to danger. Educational interventions could target these factors in ongoing waves of the pandemic or future catastrophes.